Histomorphometric analysis of the endothelial cell in skin microvasculature among diabetic foot ulcer patients - Mohd Radzuan, Hazulin; Myint, Yi Yi; Tun, Ye; Zulkifly, Ahmad Hafiz (Microscopy Society of Malaysia, 2012)

(untitled)
Introduction This study was conducted to described the histological changes occurred in skin microvessels of diabetic foot patients who were categorized as having neuropathic and neuroischemic ulcer, particularly the character of the endothelial cells, with regards to its number and thickness. Methods The study involved 3 groups with 10 subjects in each category, which is the control, the neuropathic ulcer diabetic foot patients and the neuroischemic ulcer diabetic foot patients. They were examine for the quality of peripheral pulses, ankle-brachial index measurement and fulfilled the criteria for The Neuropathy Symptoms Score and The Modified Neuropathy Disability Score. The specimens were taken using skin punch biopsy and were routinely processed for light microscopy. Then, 3 arterioles were identified for each slide of every patient. The mean endothelial cell count (ECC) was performed by calculating all the endothelial cells of the 3 arterioles and the mean endothelial cell thicknesses (ECT) of all endothelia in these selected arterioles were measured by the image analyzer. Statistical Analysis Data were analyzed using the SPSS version 18. The difference in mean ECC and ECT among neuropathic and neuroischemic ulcer patients with controls were tested using Kruskal Wallis test. p-value of less than 0.05 was taken as statistically significant. Results Histomorphometric analysis on light microscopy showed there was a significant difference between the ECC and ECT in between the control, neuropathic and neuroischemic group (p<0.05). Furthermore, the mean ranks for ECC among control subjects was significantly two times higher than the other groups and the mean ranks for ECT for the diseased groups were more than two times higher than the control. Conclusion The decrement of ECC and the increment of ECT among diabetic foot patients in general as compared to controls subject could be due to the alteration in the endothelial cell function and structure as the results of the metabolic disease. Induction of endothelial cell apoptosis and reduction in stimulation of vascular endothelial growth factor are just some of the example consequences initiated by oxidative stress.